2012
DOI: 10.1007/s10974-012-9329-2
|View full text |Cite
|
Sign up to set email alerts
|

Molluscan smooth catch muscle contains calponin but not caldesmon

Abstract: We isolated Ca(2+)-regulated thin filaments from the smooth muscle of the mussel Crenomytilus grayanus and studied the protein composition of different preparations from this muscle: whole muscle, heat-stable extract, fractions from heat-stable extract, thin filaments and intermediate stages of thin filaments purification. Among the protein components of the above-listed preparations, we did not find caldesmon (CaD), although two isoforms of a calponin-like (CaP-like) protein, which along with CaD is character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…2) [28]. It has been reported that mussel calponin inhibits Mg 2+ -ATPase activity in catch muscle actomyosin [6,7]. These findings suggest that molluscan calponin might regulate muscle contraction in a similar way to vertebrate smooth muscle.…”
Section: Discussionmentioning
confidence: 82%
“…2) [28]. It has been reported that mussel calponin inhibits Mg 2+ -ATPase activity in catch muscle actomyosin [6,7]. These findings suggest that molluscan calponin might regulate muscle contraction in a similar way to vertebrate smooth muscle.…”
Section: Discussionmentioning
confidence: 82%
“…So, the situation appears to be more complicated: the differences in the degree of activation might be attributed to both the myosin component and the actin component. The actin-binding proteins of mussel thin filaments are tropomyosin, calponin, troponin components and a few non-identified minor polypeptide [8,13]. Testing of the proteins listed above has revealed that the inhibiting effect is exerted by mussel tropomyosin.…”
Section: Resultsmentioning
confidence: 99%
“…Mussel thin filaments, mussel myosin and mussel tropomyosin were prepared as described previously [8,10]. The rabbit skeletal muscle actin of Straub type was prepared according to Rees and Yang [11], rabbit skeletal muscle myosin was prepared according to Margossian and Lowey [12].…”
Section: Proteins Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…Both catch hypotheses involve participation of thin filaments in this phenomenon. To date, the composition of proteins in thin filaments of the catch muscle is fairly well studied [8], and methods have been developed for isolation of these proteins: natural actin [9], tropomyosin [10], troponin [11], calponin [12], filamin [13], α-actinin [14]. In this work, we isolated and purified the main proteins of thin filaments, actin and tropomyosin, from the catch muscle of bivalve and from the skeletal muscles of vertebrates.…”
Section: Introductionmentioning
confidence: 99%